PROKRASTINASI AKADEMIK DITINJAU DARI MOTIVASI BERPRESTASI DAN STRES MAHASISWA - Rumiani, . (Jurnal Psikologi, 2006)
This research aimed to find out whether variables need for achievement and students stress having correlation with variable academic procrastination. Hypotheses proposed were there’s negative correlation between need for achievement and academic procrastination by controlling variable student stress and student stress is having positive correlation with academic procrastination by controlling need for achievement. Data collected through need for achievement scale, student stress scale and academic procrastination scale. 112 students of UII were involved  in this study. Data analyzed by partial correlation has proved  that need for achievement is having negative correlation with r score was – 0.5508 with p level at <0.01, meanwhile the students stress didn’t have correlation with academic procrastination with r -0.0153 with p level at > 0.05. Keywords: need for achievement, students stress, academic procrastination